Representations and Meanings of Adult Education Staff Evaluation. A Pedagogical Reflection on Six Case Studies - Palmieri, Cristina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper deals with six case studies of evaluation, which were discussed at the Mobility Workshop organized in the context of the EduEval Project (Evaluation for the Professional Development of Adult Education Staff, LLP Grundtvig).This paper depicts the different representations of evaluation explicitly and implicitly present. The aim of the article is twofold. First, it explores the meanings associated with the evaluation practicesdescribed, and it identifies both transversal and specific components. Second, it critically reflects on how evaluation may sustain and/or develop the competences of Adult Education Staff,in the light of the current pedagogical debate on the theme.